A systematic review of the teacher expectation literature over the past 30 years. Issue 3 (3rd April 2018) - Wang, Shengnan; Rubie-Davies, Christine M.; Meissel, Kane
ABSTRACT: This review aimed to illustrate the development in the teacher expectation literature and discuss the major avenues of research in the teacher expectation field from 1989 to 2018. Four analytical themes emerged from a narrative synthesis based on a systematic literature search: (1) influential factors on teacher expectations; (2) mediation mechanism of teacher expectations; (3) moderating factors of teacher expectation effects; (4) teacher expectation effects on student socio-psychological, behavioural, and achievement outcomes. On the whole, most studies confirmed earlier research findings regarding the 4 themes, although there were some studies that found results contradicting earlier work. In addition, new research topics and directions raised in the past 3 decades were identified in this review, especially regarding the mediation of teacher expectations and the socio-psychological and behavioural outcomes of the expectation effects. The review concludes with a set of recommendations for future research directions on teacher expectations.